(untitled) (Iranian Journal of Kidney Diseases, 2011)
Introduction. Upregulation of interleukin-2 may be involved, not only in the pathophysiology of nephrotic syndrome, but also in steroid resistance treatment, by increasing expression of multidrug resistant gene-1 (MDR1) gene on lymphocytes and its product P-glycoprotein effluxing corticosteroid. Our aim was to assess the relation of serum soluble interleukin-2 receptor (sIL2R) levels and MDR1 gene expression on lymphocytes with nephrotic syndrome and its corticosteroids therapy. Materials and Methods. We examined 40 children with nephrotic syndrome (15 cases of recent onset and 25 known cases with relapse) and 20 healthy children as a control group. We examined every patient twice at the time of disease activity and within 1 week of remission. Results. A significant increase was found in sIL2R level and MDR1 gene in the patients in comparison with the control group whether in activity or remission, and they were significantly higher in activity than in remission. Levels of sIL2R and MDR1 gene expression in different subgroups were higher in known cases with relapse than in new onsets, both in activity and remission, and relatively higher in steroid-resistant than in steroid-sensitive ones. Conclusions. We propose sIL2R and MDR1gene expression levels as early predictors of steroid resistance in nephrotic syndrome for early control of disease by immediate introduction of cytotoxic drugs. This is the first report providing new insight into the use of sIL2R as a predictor of steroid resistance. Thus, wide-scale studies are needed to determine a cutoff level of sIL2R above which cytotoxic drugs are introduced.